Students’ perception of team-based learning: evidence in Economics - Abío, Gemma; Alcañiz, Manuela; Gómez-Puig, Marta; Ortiz-Gracia, Luis; Royuela, Vicente; Rubert, Glòria; Serrano, Mònica; Stoyanova, Alexandrina (International Journal of Educational Innovation and Research, 2023)
Today’s new teaching and learning methodologies in higher education have moved the center from teacher to student and from teaching to learning. Since Team-Based Learning (TBL) is one of the most frequently used active learning methodologies that have emerged, the objective of this paper is to analyze and evaluate students’ perception of this methodology. To that end, first we study the positive and negative aspects of TBL considered by students. Then, we define a synthetic indicator to evaluate the degree of satisfaction of students with this methodology and analyze it according to sociodemographic variables. Finally, we analyze whether there is any correlation between the degree of satisfaction of each student and their individual final grade in global terms. The analysis is performed using a database (which includes information of 657 students) created by merging two datasets: an online questionnaire answered by students, and academic and sociodemographic information of the students who participated in the questionnaire. The main results show that TBL is perceived as a positive methodology, with respect to improving teamwork abilities. Significant differences in several competences were found by age groups, between students with or without a paid job, and depending on the educational attainment of their parents. The students’ perception of TBL regarding motivation and performance during the learning process gives information about the sociodemographic characteristics of the students who will show greater acceptance and appreciation of the introduction of TBL.